Forecasting space weather.
With more than 1,000 satellites in orbit around Earth, figuring out how to predict solar storms has been high on the research agenda. A new European system has responded to the challenge and now provides frequent and reliable web-based forecasts so that satellite operators can take action to protect their satellites from damaging solar eruptive activity.